Development of inherent safety benefits index to analyse the impact of inherent safety implementation - Zainal Abidin, M. (Institution of Chemical Engineers, 2018)
Over the years notable accidents have occurred in the chemical process industry thus creating a major concern for the safeness of its operation. The disasters led to the dire consequences that claimed human life and health as well as monetary losses. Inherently safer design is an effective solution to prevent accidents because it postulates that the best way to reduce risk is to avoid the hazard rather than control the hazard. Although the implementation of inherently safer design can give great advantages and cost optimal operation throughout process's life cycle, slow adoption of this principle into real design practice can be observed. This is partly because the inability to realise the benefits of inherent safety implementation among industrial practitioner. This paper presents a methodology for evaluating inherently safer design alternatives and identifying the benefits using an index-based approach at preliminary design stage. The proposed methodology is applied to ammonia storage with the objective of preventing and minimising toxic release. The results have shown that the new methodology can identify the best inherently safer design and the benefits where it is capable to reduce the severity of accident and the requirement to manage hazardous process. Â© 2018 The Institution of Chemical Engineers